2008
DOI: 10.1088/0953-2048/21/9/092004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for supercurrent connectivity in conglomerate particles in NdFeAsO1−δ

Abstract: Here we use global and local magnetometry and Hall probe imaging to investigate the electromagnetic connectivity of the superconducting current path in the oxygendeficient fluorine-free Nd-based oxypnictides. High resolution transmission electron microscopy and scanning electron microscopy show strongly-layered crystallites, evidence for a ~ 5nm amorphous oxide around individual particles, and second phase neodymium oxide which may be responsible for the large paramagnetic background at high field and at high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
48
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 21 publications
(28 reference statements)
11
48
0
Order By: Relevance
“…Global supercurrent flow [18], locally well-connected area [24] and intrinsic strong links [22,23,25,26] were confirmed to exist in this system.…”
Section: Introductionmentioning
confidence: 57%
“…Global supercurrent flow [18], locally well-connected area [24] and intrinsic strong links [22,23,25,26] were confirmed to exist in this system.…”
Section: Introductionmentioning
confidence: 57%
“…The second peak effect has been observed and reported in polycrystalline samples of the FeAs-1111 phase 19,20,21,22 . However, it has not been reported in the FeAs-122 phase either in polycrystalline or single crystal samples.…”
mentioning
confidence: 53%
“…The discovery of superconductivity in the LaFeAsO 1-x F x compound [1] has been followed by rapid exploration of many aspects of the superconducting behaviour of the broad class of rare earth iron oxypnictides [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] whose transition temperature T c can reach above 40 K when La is replaced by Ce [5] and above 50 K when the rare earth is Pr, Nd, Sm and Gd [7][8][9][10][11]. Hunte et al reported that even the La Fe-oxypnictide with Tc ~ 26 K exhibits a very high upper critical field H c2 of ~65 T [6] while H c2 over 200 T was deduced for the Sm and Nd Fe-oxypnictides [17], strongly suggesting a large high field domain for the Fe-oxypnictides.…”
Section: Introductionmentioning
confidence: 99%
“…Foreseeing practical applications, there has been immediate interest in the critical current density too. But all polycrystalline samples of La, Sm and Nd Fe-oxypnictides [12][13][14][15][16] examined to date show signs of less than full grain-to-grain connectivity, raising the same concern of depression of superconducting order parameter at grain boundaries that has so greatly complicated applications of the cuprates [18]. Grain boundary order parameter suppression is fundamental detriment to applications since it means that a randomly aligned grain structure will not pass the full current that can be sustained by intragrain vortex pinning, thus reducing the global or whole-sample current density below that circulating in the grains.…”
Section: Introductionmentioning
confidence: 99%